The impact of personality and approaches to learning on information behaviour (Information Research: An International Electronic Journal)
Previous studies have shown how personality influences learning strategies and learning outcome. In this study this will be taken further by combining personality and approaches to learning with information behaviour. The aim of this study is to show how the five traits of the Five-Factor Inventory related to the approaches to learning of the ASSIST-test affect information behaviour. The subjects will be approximately 500 university students writing their dissertation. In a pilot study it was shown that personality traits can be related to approaches to learning. Moreover they seem to form distinctive information behaviour.